A Tournament Approach to Price Discovery in the U.S. Cattle Market. (10th February 2021) - Wright, Jeffrey; Kim, Man-Keun; Tejeda, Hernan A.; Kim, Hwa-Neyon
Abstract: The dominant market where information is discovered plays the role of price leader providing substantial market information to other markets. This study investigates the dynamic relationships of 30 cattle markets across regions, cattle types, and cash/futures markets. The comparison of many markets, using an error correction model, is accomplished with the introduction of a tournament with a hierarchical cluster analysis, which allows us to conclude that the leading price for the U.S. cattle markets is discovered in the futures markets for both feeder and fed cattle.